Identification and In Vitro Expansion of Buccal Epithelial Cells. Issue 6 (June 2018) - Ghaemi, Soraya Rasi; Delalat, Bahman; Harding, Frances J.; Irani, Yazad D.; Williams, Keryn A.; Voelcker, Nicolas H.
Ex vivo -expanded buccal mucosal epithelial (BME) cell transplantation has been used to reconstruct the ocular surface. Methods for enrichment and maintenance of BME progenitor cells in ex vivo cultures may improve the outcome of BME cell transplantation. However, the parameter of cell seeding density in this context has largely been neglected. This study investigates how varying cell seeding density influences BME cell proliferation and differentiation on tissue culture polystyrene (TCPS). The highest cell proliferation activity was seen when cells were seeded at 5×10 4 cells/cm 2 . Both below and above this density, the cell proliferation rate decreased sharply. Differential immunofluorescence analysis of surface markers associated with the BME progenitor cell population (p63, CK19, and ABCG2), the differentiated cell marker CK10 and connexin 50 (Cx50) revealed that the initial cell seeding density also significantly affected the progenitor cell marker expression profile. Hence, this study demonstrates that seeding density has a profound effect on the proliferation and differentiation of BME stem cells in vitro, and this is relevant to downstream cell therapy applications.